Hyalinizing trabecular tumor of the thyroid: a clinicopathological analysis of four cases and review of the literature - Liu, Yufei (Int J Clin Exp Pathol, 2017)
Objective: To explore the clinicopathological features, diagnosis and differential diagnosis of hyalinizing trabecular tumor (HTT) of the thyroid. Methods: The four HTT specimens were collected including demographics, clinical information, relevant images, the extent of thyroidectomy, the follow-up and representative pathological data of tumors were available for analysis. In addition, the immumohistochemical staining related to the tumor as well as the BRAF and N-ras mutation analysis were analysed. Results: The mean age of four patients was 47 years old and the mean size of the tumor was 2.8 cm. Most of the patients were asymptomatic, while detecting incidentally by using neck ultrasound test. Ultrasound imaging of all cases showed demarcated substantial hypoechoic nodules in ipsilateral thyroid lobe. Computed Tomography (CT) showed a clear low density shadow in the affected thyroid lobe. Tumors of three cases were located at the left, but the other one was located at the right thyroid gland with a complete fibrous capsule. The cytological features resembled papillary thyroid carcinoma (PTC). The histological test indicated that the tumors had characteristic of trabecular growth pattern with hyalinizing material. The tumor cells were in shape of polygonal, oval or high columnar with an acidophilic or clear cytoplasm. The nuclei were oval with inconspicuous small nucleoli, prominent grooves and pseudoinclusion body in cell nucleus. Mitosis and psammoma bodies were rare to be observed. Cytoplasmic “yellow bodies” were frequently observed. The hyaline material was prominent, with positive periodic acid-Schiff (PAS) and negative Congo red staining. Immunohistochemically, tumor cells were positive for thyroglobulin (Tg), thyroid transcription factor-1 (TTF-1), CD56 and negative for calcitonin, cytokeratin 19 (CK19), HBME-1, S-100 and synaptophysin (SyN). Chromogranin A (CgA) and galectin-3 were expressed weakly in some cases. Staining with the MIB-1 antibody showed membranous/cytoplasmic immunoreactivity. Whereas, another clone of Ki-67 (SP6) showed a common nuclear pattern with an index of <1%. None of the four cases exhibited the BRAF V600E protein reactivity. Gene mutation analysis demonstrated no BRAF and N-ras mutation. There was no evidence of local recurrence or metastasis after 6 to 36 months of follow-up. Conclusions: HTT is an uncommon thyroid tumor with very low malignant potential. It has no particular clinical features, so it’s often misdiagnosed in fine needle aspiration cytology (FNAC)/Ultrasonography-guided fine needle aspiration cytology (US-FNAC) and frozen section (FS). Its final diagnosis mainly relies on typical histopathological features and characteristic expression pattern of MIB-1 immunohistochemical staining.